Relationships between forest cover and fish diversity in the Amazon River floodplain. Issue 1 (4th September 2017) - Arantes, Caroline C.; Winemiller, Kirk O.; Petrere, Miguel; Castello, Leandro; Hess, Laura L.; Freitas, Carlos E. C.
Abstract: Habitat degradation leads to biodiversity loss and concomitant changes in ecosystem processes. Tropical river floodplains are highly threatened by land cover changes and support high biodiversity and important ecosystem services, but the extent to which changes in floodplain land cover affect fish biodiversity remains unknown. We combined fish and environmental data collected in situ and satellite‐mapped landscape features to evaluate how fish species with different ecological strategies and assemblage structures respond to deforestation in floodplains of the Amazon River. We surveyed 462 floodplain habitats distributed along a gradient of land cover, from largely forested to severely deforested. Rather than analyse only taxonomic metrics, we employed an integrative approach that simultaneously considers different aspects of fish biodiversity (i.e. β diversity and taxonomic and functional assemblage structure) to facilitate mechanistic interpretations of the influence of land cover. Spatial patterns of fish biodiversity in the Amazon River floodplain were strongly associated with forest cover as well as local environmental conditions linked to landscape gradients. Several species and functional groups defined by life‐history, feeding, swimming/microhabitat‐use strategies were positively associated with forest cover. Other species, including some that would usually be considered habitat generalists and species directly dependent on autochthonous resources (e.g. planktivores), were most common in areas dominated by herbaceous vegetation or open water habitats associated with the opposite extreme of the forest cover gradient. β diversity and the degree of uniqueness of species combinations within habitats were also positively associated with forest cover. Synthesis and applications . Our results demonstrating that spatial patterns of fish biodiversity are associated with forest cover, indicate that deforestation of floodplains of the Amazon River results in spatial homogenization of fish assemblages and reduced functional diversity at both local and regional scales. Floodplains world‐wide have undergone major land cover changes, with forest loss projected to increase during the next decades. Conserving fish diversity in these ecosystems requires protecting mosaics of both aquatic habitats and floodplain vegetation, with sufficient forest cover being critically important. Abstract : Our results demonstrating that spatial patterns of fish biodiversity are associated with forest cover, indicate that deforestation of floodplains of the Amazon River results in spatial homogenization of fish assemblages and reduced functional diversity at both local and regional scales. Floodplains world‐wide have undergone major land cover changes, with forest loss projected to increase during the next decades. Conserving fish diversity in these ecosystems requires protecting mosaics of both aquatic habitats and floodplain vegetation, with sufficient forest cover being critically important.